Using modified Chebyshev functions for approximation in 5G technologies - Yerzhan, Assel; Nakisbekova, Balausa; Manbetova, Zhanat; Boykachev, Pavel; Imankul, Manat; Dzhanuzakova, Raushan; Shedreyeva, Indira; Karnakova, Gaini (Institute of Advanced Engineering and Science, 2024)
This research addresses the critical challenge of broadband matching in radio engineering, focusing on enhancing phase-frequency response (PFC) linearity across wide frequency bands. A novel approach, utilizing modified Chebyshev functions, demonstrates significant potential in reducing phase distortions within 5G technology applications. Unlike traditional Chebyshev functions, this method incorporates strategically placed transmission zeros— complex conjugate pairs on the s-variable complex plane—without increasing the filter circuit's order. This innovation results in a low-order filter circuit characterized by uniform phase response and group delay characteristics (GDT), offering an effective solution for matching circuit design with less phase-frequency distortion and improved group delay uniformity across diverse load conditions. The modified Chebyshev approximation outperforms its classical counterpart in both phase linearity and selectivity within the 1 to 1.2 cutoff frequency range. This enhancement is crucial for the development of low-frequency filters, with broader implications for creating high-frequency, band-pass, and band-stop filters via known frequency transformations. Empirical results validate the proposed method's reliability and effectiveness, marking a significant advancement in the field of radio engineering by addressing broadband matching challenges with increased efficiency and simplified design implementations.